2016
DOI: 10.1002/pat.3970
|View full text |Cite
|
Sign up to set email alerts
|

PEG-dialdehyde-the new cross-linking agent for collagen/elastin hydrogels

Abstract: Collagen and elastin are the major proteins of an extracellular matrix. They possess attractive, complementary mechanical properties in their native state, but during isolation, its unique structure is destroyed, which affects the parameters of the materials. However, they still have excellent biological properties. The cross-linking process improves the physicochemical properties of protein materials. The ideal cross-linking agent should be effective and does not impair the biological properties of the materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Collagen hydrogels were proposed for 3D multicellular microfluidic chip construction applied in an in vitro skin model which can function as a more physiologically realistic platform for testing skin reactions to cosmetic products and drugs [16]. Collagen-based hydrogels can be cross-linked with EDC/ NHS, starch dialdehyde, tannic acid, squaric acid, PEG-dialdehyde UV radiation and many other cross-linking agents [17][18][19][20][21].…”
Section: Collagen In Cosmeticsmentioning
confidence: 99%
“…Collagen hydrogels were proposed for 3D multicellular microfluidic chip construction applied in an in vitro skin model which can function as a more physiologically realistic platform for testing skin reactions to cosmetic products and drugs [16]. Collagen-based hydrogels can be cross-linked with EDC/ NHS, starch dialdehyde, tannic acid, squaric acid, PEG-dialdehyde UV radiation and many other cross-linking agents [17][18][19][20][21].…”
Section: Collagen In Cosmeticsmentioning
confidence: 99%
“…This may also be the cause of low cytotoxicity results obtained for our nontreated hAM and, as a consequence, also for cross-linked materials. Our previous works showed that the cross-linking factors used in this research support cells' attachment and growth when used for collagen, elastin, or gelatin crosslinking, and they can be applied for modification of biomaterials for tissue regeneration and used as a safe alternative for popular cross-linking agents [18][19][20]27]. We expect a similar effect in the case of hAM modification, but further studies should be conducted considering how the amniotic membrane is stored.…”
Section: Discussionmentioning
confidence: 64%
“…This is proved by the increase in the thermal degradation temperature of cross-linked materials, as well as the changes observed in the FTIR spectra. The increase in Amide I and Amide II intensity indicates the formation of new amide bonds as a result of reactions between aldehyde groups of DAS, PEG-A, and amino groups of hAM [18,19], and also mediated by EDC/NHS and PEG-NHS [4]. As a result, the mechanical strength of cross-linked human amniotic membranes is improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other natural macromolecules can be introduced to obtain COL‐based composites with better properties. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%